Technological Advances of 3D Scaffold-Based Stem Cell/Exosome Therapy in Tissues and Organs - Gu, Chenyang; Feng, Jia; Waqas, Ahmed; Deng, Yushu; Zhang, Yifan; Chen, Wanghao; Long, Jun; Huang, Shiying; Chen, Lukui (Frontiers in Cell and Developmental Biology, 2021)
Recently, biomaterial scaffolds have been widely applied in the field of tissue engineering and regenerative medicine. Due to different production methods, unique types of three-dimensional (3D) scaffolds can be fabricated to meet the structural characteristics of tissues and organs, and provide suitable 3D microenvironments. The therapeutic effects of stem cell (SC) therapy in tissues and organs are considerable and have attracted the attention of academic researchers worldwide. However, due to the limitations and challenges of SC therapy, exosome therapy can be used for basic research and clinical translation. The review briefly introduces the materials (nature or polymer), shapes (hydrogels, particles and porous solids) and fabrication methods (crosslinking or bioprinting) of 3D scaffolds, and describes the recent progress in SC/exosome therapy with 3D scaffolds over the past 5 years (2016–2020). Normal SC/exosome therapy can improve the structure and function of diseased and damaged tissues and organs. In addition, 3D scaffold-based SC/exosome therapy can significantly improve the structure and function cardiac and neural tissues for the treatment of various refractory diseases. Besides, exosome therapy has the same therapeutic effects as SC therapy but without the disadvantages. Hence, 3D scaffold therapy provides an alternative strategy for treatment of refractory and incurable diseases and has entered a transformation period from basic research into clinical translation as a viable therapeutic option in the future.